In vitro litholytic effect of commonly used siddha drugs and the aqueous extract of Tribulus terrestris as an adjuvant on oxalate stone - Minfak, K.A.; Sivagnanam, S.; Arasaratnam, V. (University of Jeyewardenepura, 2014)
Urolithiasis is a disease that forms stones in any part of the urinary tract, composed of organic matrix and organic and/ or inorganic crystalloids. Even though there were several medical and surgical interventions to treat, patients prefer Siddha drugs as they have fewer adverse effects. The adjuvant Tribulus terrestris is used commonly because of its' highest dissolution of calcium oxalate, as oxalate stones are the typical type found in Sri Lanka.